Structure determination of a tetrahydro-beta-carboline of arthropod origin: A novel alkaloid-toxin subclass from the web of spider Nephila clavipes - Marques, M. R.; Mendes, M. A.; Tormena, C. F.; Souza, B. M.; Cesar, LMM; Rittner, R.; Palma, Mario Sergio [UNESP] (Verlag Helvetica Chimica Acta Ag, 2005)
The orb-web spiders are polyphagous animals in which the web plays a very important role in the capture of preys; oily droplets usually cover the capture-web of the spider Nephila clavipes and seem to be of great importance for prey capture. The knowledge of the chemical composition of these droplets is necessary to understand the function of this adhesive material in web mechanics and prey capture. A novel subclass of spider toxins, tetrahydro-beta-carboline, was identified among the weaponry of compounds present inside of oily droplets. This type of alkaloid is not common among the natural compounds of spider toxins. Apparently, when the prey arthropods get caught by the spider web, their bodies are covered with many adhesive oily droplets, which disrupt delivering the tetrahydro-beta-carboline to the direct contact with the prey integument. Toxicity assays demonstrated a potent lethal effect of the alkaloid toxin to the spider preys; topical applications of the teirahydro-beta-carboline at first caused clear signs of neurotoxicity, followed by the death of preys. The structure of the major component, a tetrahydro-beta-carboline, among the alkaloid toxins was elucidated by means of UV spectrophotometry, ESI mass spectrometry, H-1-NMR spectroscopy, and high-resolution mass spectrometry. The structure of the natural toxin was determined as 1-(2-guanidinoethyl)-1,2,3,4-tetrahydro-6-hydroxymethyl)-beta-carboline; the investigation of the pharmacological properties and neurotoxic actions of this compound may be used in the future as reference for the development of new drugs to be applied at level of pest control in agriculture.